2015
DOI: 10.1590/1414-431x20154583
|View full text |Cite
|
Sign up to set email alerts
|

Activation of endogenous angiotensin converting enzyme 2 prevents early injuries induced by hyperglycemia in rat retina

Abstract: Diabetic retinopathy (DR) is a serious complication of diabetes mellitus that may result in blindness. We evaluated the effects of activation of endogenous angiotensin converting enzyme (ACE) 2 on the early stages of DR. Rats were administered an intravenous injection of streptozotocin to induce hyperglycemia.] oxy]-9H-xanthone 9 (XNT) was administered by daily gavage. The death of retinal ganglion cells (RGC) was evaluated in histological sections, and retinal ACE2, caspase-3, and vascular endothelial growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 37 publications
3
32
1
Order By: Relevance
“…This hypothesis is supported by the biological action of a novel receptor (P)RR, a part of the RAS signaling, which is present in retinal Muller cells, 42 which is a site of VEGF synthesis and its tyrosine kinase receptors, 126 indicating an independent role in the pathogenesis of DR. Further studies provide the evidence that (P)RR triggers the expression of angiogenic molecules, including VEGF/VEGFR2, ERK1/2 and TGFβ1 in the retinal cells and leads to DR, which was abolished by (P)RR/ERK signaling blockade 83, 84, 85, 86. Recently Foureaux et al found that the activation of ACE2 reduced the death of retinal ganglion cells in hyperglycemic rats 87 . The overall findings suggest that the RAS is strongly involved in the pathogenesis of DR and inhibition of these RAS signaling events may have a beneficial effects on the reduction and prevention of DR and improves aspects of vascular and neuroglial injury in diabetic retina.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This hypothesis is supported by the biological action of a novel receptor (P)RR, a part of the RAS signaling, which is present in retinal Muller cells, 42 which is a site of VEGF synthesis and its tyrosine kinase receptors, 126 indicating an independent role in the pathogenesis of DR. Further studies provide the evidence that (P)RR triggers the expression of angiogenic molecules, including VEGF/VEGFR2, ERK1/2 and TGFβ1 in the retinal cells and leads to DR, which was abolished by (P)RR/ERK signaling blockade 83, 84, 85, 86. Recently Foureaux et al found that the activation of ACE2 reduced the death of retinal ganglion cells in hyperglycemic rats 87 . The overall findings suggest that the RAS is strongly involved in the pathogenesis of DR and inhibition of these RAS signaling events may have a beneficial effects on the reduction and prevention of DR and improves aspects of vascular and neuroglial injury in diabetic retina.…”
Section: Resultsmentioning
confidence: 91%
“…Thereby, Mas receptor activator, angiotensin (1–7), 49 and ACE2 activator, diminazene aceturate (DIZE)87, 97 showed beneficial effects for glaucoma management via a decrease in IOP. These findings indicate that RAS inhibition may be effective for treatment of glaucoma.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed the upregulation of ACE2/Ang-(1-7)/MasR axis which contribute to protective roles associated with complications in diabetic eyes [27, 6971]. However, the impact of the vasoprotective axis of the ACE2/Ang-(1-7)/MasR in diabetic patient with DR remains poorly understood.…”
Section: Ace2/ang-(1-7)/mas Receptor Axis In Drmentioning
confidence: 99%
“…The appearance of empty spaces may be due to phagocytosis of the apoptotic retinal neurons by glial cells [31,47]. Also, the reduction in the number of ganglion cells was in agreement with Foureaux, et al (2015) [48]. This can be explained by apoptosis of ganglion cells but to a lesser degree than in the other retinal layers [49].…”
Section: Discussionmentioning
confidence: 81%